Optimalisasi Pendidikan Kesehatan Remaja: Pencegahan Penyakit Menular Seksual dan Pembentukan Gaya Hidup Sehat - Fitri; Aminah; Eka Yulia Dithah; Fathul Maysarah Syahab; Haekal Tradana Saputra; Ida Diah Pahdila Wahyu Pebiana; Lusmiati; Regita Zsalsabila Rahma; Reza Wira Sanjaya; Selma Aqila Malwani; Siti Nur Rahmadani; Sri Wahyuni; M Bachtiar Safrudin (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2026)
This community service activity aimed to increase adolescents’ knowledge and awareness regarding the prevention of sexually transmitted diseases (STDs) and the formation of a healthy lifestyle among students of SMK 12 Loa Buah, Samarinda City. The implementation method used a participatory health education approach consisting of preparation, implementation, and evaluation stages. The activity began with a pre-test to assess students’ baseline knowledge, followed by health education delivered through interactive lectures, discussions, and question-and-answer sessions, and concluded with a post-test for evaluation. The participants were 60 students from grades X and XI. The results showed a significant improvement in knowledge, with the “good” knowledge category increasing from 80% in the pre-test to 100% in the post-test. In addition to improved knowledge, participants also demonstrated positive attitudes toward the adoption of clean and healthy living behaviors in daily life. In conclusion, school-based health education using a participatory approach is effective in improving adolescent health literacy and encouraging the formation of a healthy lifestyle. This program is recommended to be implemented continuously through School Health Unit (UKS) activities.